Answer:
The equation of hyperbola with vertices at (0,±6) and asypmtotes at
![y= ±(3)/(2) x](https://img.qammunity.org/2019/formulas/mathematics/high-school/qwlbap7mo0pqz1dm66e80d5thk6e5ofof4.png)
Explanation:
Given
vertices of hyperbola at (0,±6)
It means hyperbola along y axis and centre at (0,0)
Asymptotes
![y=±(3)/(2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/djhdogwz1e2cdyoj1cnlugq9hix8dip8px.png)
We know that equation of hyperbola along y axis
![(y^2)/(a^2) -(x^2)/(b^2) =1](https://img.qammunity.org/2019/formulas/mathematics/high-school/6zp1tj5umrq5uxuy1zkgsz9te726i74abt.png)
a=6
We know that the general equation of hyperbola asymptotes and vertcal transverse axis
y=
![±(a)/(b) x](https://img.qammunity.org/2019/formulas/mathematics/high-school/68s5w1eqflwmkz25uq49a7k7ruscz8p8pf.png)
=
![(6)/(b) x](https://img.qammunity.org/2019/formulas/mathematics/high-school/fmh71bricylcj0u96otax96erwlnv0im0b.png)
Both side cancel x we get
![b=(6*2)/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/npylddmmk8hx191tkm4hlvbnt5991az6qw.png)
b=4
When we take
}{b}x[/tex]
Then we get b=4
Now, put the value of a and b in the equation of hyperbola we get
=1
![(y^2)/(36) -(x^2)/(16) =1](https://img.qammunity.org/2019/formulas/mathematics/high-school/1sy0po2l59dgwxwqhn0wntv2frdxo0f87q.png)
Hence, the required standard equation of hyperbola
.